Does Decision-Making Ability Predict HIV-Associated Neurocognitive Disorder?. (30th August 2019) - Summers, A C; Morris, A; Savin, M J; Aghvinian, M; Crook, C; Byrd, D; Rivera Mindt, M
Abstract: Background: Executive dysfunction (EF) in people living with HIV (PLWH) is well-established. However, decision-making, a key aspect of EF, is often overlooked in neurocognitive (NC) evaluations of PLWH. Poor decision-making can detrimentally impact PLWH by increasing risk of poor health outcomes. This study aimed to determine if including a decision-making task in NC evaluations might improve diagnostic formulations. Participants and Method: This cross-sectional study included 90 PLWH (63 Latinx; 27 non-Latinx white) who were evaluated for HIV-Associated Neurocognitive Disorder (HAND) using established criteria, with the Wisconsin Card Sorting Test (WCST) and Trail Making Test Part B (TMTB) comprising the "traditional" EF domain. The Iowa Gambling Task (IGT) assessed decision-making. Demographically corrected T-scores were calculated for each test. The "traditional" EF tests were averaged into an EF domain T-score. The WCST, TMTB, and IGT were also averaged into a "new" EF+IGT domain T-score. Results: The new EF+IGT domain T-score significantly predicted HAND diagnosis (R^2 = .14, p < .001). However, using hierarchical regression, the "traditional" EF domain (WCST and TMTB) also significantly predicted HAND (R^2 = .18, p < .001) and adding the IGT Total T-score did not contribute unique variance to the model (R^2 = .18, p < .001; R^2Δ < .001, pΔ = .92). Conclusions: A new combined EF domain T-score that included decision-making was a significant predictor of HAND diagnosis. However, adding IGT Total Score did not enhance HAND diagnosis compared to "traditional" EF measurement, indicating that the "traditional" EF domain adequately informs HAND diagnosis. A limitation of this study was the small sample size. Given the important health implications of decision-making in PLWH, future research, with a larger sample size is warranted to better conceptualize how decision-making can be incorporated into diagnostic formulations for PLWH.